An integrated strategy for profiling the chemical components of Scutellariae Radix and their exogenous substances in rats by ultra‐high‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry. (29th July 2020) - Zhang, Fengxiang; Li, Ziting; Li, Min; Yuan, Yulinglan; Cui, Shuangshuang; Chen, Jiaxu; Li, Ruiman
Abstract : Rationale: Traditional Chinese medicines (TCMs) attract worldwide attention because of their effects in clinical application recorded in China historical ancient codes and in records, such as 'Treatise on Febrile Diseases'. With the developments of drug analysis and research, evaluating the in vivo substances in TCMs has become of great importance. Scutellariae Radix (SR, named as huang‐qing in China), the root of Scutellaria baicalensis Georgi, has shown favorable clinical effects and safety in the treatment of infection diseases; however, its in vivo compounds are unclear and need detailed investigation. Methods: An ultra‐high‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry (UHPLC/QTOF MS) method coupled to an integrated strategy involving diagnostic ions, neutral losses and a prediction platform was used to explore the constituents of SR, and their exogenous substances in rats. Results: A total of 118 chemical constituents mainly featuring five chemical structure types (flavone C ‐glycosides, flavone O ‐glycosides, free flavones, flavanones and phenylethanoid glycosides) were identified or tentatively characterized in SR, and 175 xenobiotics (68 prototypes and 107 metabolites) were profiled in rat plasma, urine, bile and feces after ingestion of SR. The metabolites were classified into four related chemical groups: flavone C ‐glycosides, flavone O ‐glycosides, flavanones and phenylethanoid glycosides. Phase II metabolism reactions, such as glucuronidation and sulfation, were the major metabolic reactions in addition to phase I reactions of hydrolysis and hydrogenation. The corresponding main metabolic features of SR in rats were also elucidated. Conclusions: The metabolism of SR, as a whole, was systemically revealed for the first time, and our work also provided meaningful information for pharmacokinetics studies and pharmacological analysis of SR in future work.